THE ANALYSIS OF POLYMORPHISM OF KAPPA-CASEIN, Β- LACTOGLOBULIN AND PROLACTIN GENES AMONG YAKUTIAN CATTLE AND ITS INFLUENCE ON MILK PRODUCTION - Pavlova , Nadezhda; Dodokhov , Vladimir; Filippova , Natalya; Khaldeeva , Motrena; Kurtanov , Hariton; Stepanov , Nikolaj (Cifra Ltd, 2019)
DNA samples of cows of Simmental and Kholmogory breeds served as the material for the research. Release of DNA was carried out by a standard method of phenol–chloroform extraction. Polymorphisms of rs43703015 of the CSN3 gene, rs109625649 of the LGB gene and rs134028641 of the PRL gene are studied by means of PCR-RFLP analysis. In all studied selections, the A allele prevails on the CSN3 gene. The frequency of the A allele prevailed over the frequency of the B allele on the PRL gene. The animals with the greatest milk yield and fat content of milk on the CSN3 gene had the genotype including the A allele. Depending on the LGB genotype, there was established that the largest size of milk yields have individuals with the AA and AB genotype in selections of the Simmental breed of both selections. In selection of the Kholmogory breed - with the B genotype. Adaptation process is fraught with a serious pressure, that, undoubtedly, affects the efficiency; while long-acting it leads to disorder of physiological functions. Therefore, realization of genetic potential of the delivered cattle to Yakutia will require time. Материалом исследования служили образцы ДНК коров симментальской и холмогорской пород. Выделение ДНК проводилось стандартным методом фенольно-хлороформной экстракции. С помощью ПЦР ПДРФ анализа изучены полиморфизмы rs43703015 гена CSN3, rs109625649 гена LGB и rs134028641 гена PRL. Во всех изученных выборках, по гену CSN3 преобладает аллель А. По гену LGB, во всех выборках преобладал гетерозиготный генотип АВ. По гену PRL частота аллели А преобладала над частотой аллели В. Наибольшим удоем и содержанием жира в молоке, по гену CSN3 обладали животные с генотипом несущим в себе аллель А. В зависимости от генотипа LGB, установили, что в выборках симментальской породы обоих селекций, наибольшей величиной удоев, обладают особи с генотипом АА и АВ. В выборке холмогорской породы - с генотипом ВВ. В зависимости от гена PRL, более высокими надоями обладали особи несущие в своем генотипе аллель А. Процесс адаптации ...